Measurement of the inclusive jet cross section in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Askew, A.; et al. (American Physical Society (APS), 2012)
We present a measurement of the inclusive jet cross section using the Run II cone algorithm and data collected by the D0 experiment in pp̄ collisions at a center-of-mass energy √s=1.96TeV, corresponding to an integrated luminosity of 0.70fb -1. The jet energy calibration and the method used to extract the inclusive jet cross section are described. We discuss the main uncertainties, which are dominated by the jet energy scale uncertainty. The results cover jet transverse momenta from 50GeV to 600GeV with jet rapidities in the range -2.4 to 2.4 and are compared to predictions using recent proton parton distribution functions. Studies of correlations between systematic uncertainties in transverse momentum and rapidity are presented. © 2012 American Physical Society.